2014
DOI: 10.1159/000367934
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Doublecortin-Immunopositive Cells in the Brains of Four Afrotherian Mammals: the Hottentot Golden Mole <b><i>(Amblysomus hottentotus)</i></b>, the Rock Hyrax <b><i>(Procavia capensis)</i></b>, the Eastern Rock Sengi <b><i>(Elephantulus myurus)</i></b> and the Four-Toed Sengi <b><i>(Petrodromus tetradactylus)</i></b>

Abstract: Adult neurogenesis in the mammalian brain is now a widely accepted phenomenon, typically occurring in two forebrain structures: the subgranular zone (SGZ) of the hippocampal dentate gyrus and the subventricular zone (SVZ). Until recently, the majority of studies have focused on laboratory rodents, and it is under debate whether the process of adult neurogenesis occurs outside of the SGZ and the SVZ in other mammalian species. In the present study, we investigated potential adult neurogenetic sites in the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 72 publications
1
24
0
Order By: Relevance
“…In the adult rodent neurogenic niche, the process of neuronal birth, migration, and maturation has been documented using not just marker expression and BrdU incorporation, but also genetic lineage tracing, retroviral labeling, ultrastructural characterization, and co-labeling with other cell-type markers. As these tools are not always available in all species, the expression of markers of young neurons is also used to explore new species in addition to new brain regions (Chawana et al, 2013; Patzke et al, 2013, 2014). However, it is important to keep in mind that each of these tools on their own has significant limitations.…”
Section: Widening the Search For Adult Neurogenesismentioning
confidence: 99%
“…In the adult rodent neurogenic niche, the process of neuronal birth, migration, and maturation has been documented using not just marker expression and BrdU incorporation, but also genetic lineage tracing, retroviral labeling, ultrastructural characterization, and co-labeling with other cell-type markers. As these tools are not always available in all species, the expression of markers of young neurons is also used to explore new species in addition to new brain regions (Chawana et al, 2013; Patzke et al, 2013, 2014). However, it is important to keep in mind that each of these tools on their own has significant limitations.…”
Section: Widening the Search For Adult Neurogenesismentioning
confidence: 99%
“…Further studies, which did not use proliferation markers, suggested that outside canonical neurogenic regions the DCX/PSA-NCAM IN are most abundant in layer II of the piriform cortex, entorhinal cortex, and neocortex of four afrotherian mammals (Patzke et al, 2014), young lupines (De Nevi et al, 2013), non-human primates Zhang et al, 2009;Bloch et al, 2011), and humans Mikkonen et al, 1998;Ni Dhúill et al, 1999). Although some uncertainty about the exact identity of DCX/PSA-NCAM IN in these studies resulted from the absence of BrdU administration and the variability associated with post-mortem histological analyses, the distribution and morphology of cortical cells expressing DCX and/or PSA-NCAM seemed to be comparable between these mammalian species.…”
Section: Most Cortical Dcx/psa-ncam-expressing Cells Are Immature Neumentioning
confidence: 99%
“…Inconsistencies among these studies are likely the result of technical issues as well as species specific and regional variation in the distribution and fate of cortical DCX/PSA- be standardized since they currently vary among the different studies and species investigated. Thirdly, the molecular marker used to follow the fate of DCX/PSA-NCAM IN is DCX in some studies (Xiong et al, 2008;Cai et al, 2009;Zhang et al, 2009;De Nevi et al, 2013;Patzke et al, 2014;Yang et al, 2015;), but in others is PSA-NCAM (Varea et al, 2009;Varea et al, 2011). To follow the fate of DCX/PSA-NCAM IN non-ambiguously, we recommend the use of both antibodies simultaneously in combination with Tbr1 (Luzzati et al, 2009;Rubio et al, 2015).…”
Section: The Number Of Dcx/psa-ncam In Declines Drastically With Agementioning
confidence: 99%
“…While not parcellated into distinct regions, the dentate gyrus is one of the few regions of the adult brain to maintain neurogenesis throughout much of the adult life of mammals (Kempermann, ). Adult hippocampal neurogenesis has been reported in the dentate gyrus of all mammalian species studied to date (Cavegn et al, ; Chawana et al, ; Fasemore et al, ; Kempermann, ; Patzke et al, ; Patzke et al, , ) to the exception of cetaceans, where this neural trait appears to be absent (Patzke et al, ). The six‐layered subicular complex is composed of four parts, the dorsal and ventral subiculum, presubiculum, parasubiculum, and subicular transitional cortex, while the six‐layered entorhinal cortex is most often described as being composed of medial and lateral cortical areas, but detailed analyses indicate the presence of several more cortical areas in this region (Amaral & Lavenex, ; Paxinos & Watson, ; Schulz & Engelhardt, 2014).…”
Section: Introductionmentioning
confidence: 99%